ATTITUDE AND STRATEGY OF INDEPENDENT BAND ‘BAHUREKSA’ IN CREATING MUSIC WITH THE CONCEPT OF ROOM POP - Achmad Bhisma Ayudha Suwarna; Rubby Sanjaya; Fiery Agustian Rizbani; Reza Pahlevi Sugianto; Sultan Rizky adi Perdana; Boyke Devit Adistya; Deriel Sudiro (Universitas Pendidikan Indonesia, 2022)
Music has become one of the most entertaining forms of entertainment. This is because music is very easy to digest. In addition to entertainment, music can also be a source of life for musicians. Some think that music is a necessity in their life. Then there is independent music which is the main reason for this research. Their struggle in life and making their work is very interesting to study. This is because independent music is music that is different from the industry which already has a luxury in music. Independent music carries out every process in making its work independently without any help from the industry. An example of independent music struggles studied here is the process of how they make music in simplicity. This research uses a qualitative method with a descriptive analytic approach, all data is generated through a process of observation, interviews, documentation studies and literatures to produce data that can be justified academically. This data is journalism data plus as a term for documentary films which are intended to compose a script which is then realized in making a documentary. This study found the term room pop which means the process of making music in the room. Room pop is a concept that helps indie musicians who don't have the luxury of making music into something they can do. This is because room pop does not rely on professional tools to make music. Enough with makeshift tools and adequate computers, musical works can be made. The implications of this research as the main data in making a documentary.